Optimasi Formula Tablet Ekstrak Kering Daun Jati Belanda Menggunakan Kombinasi Starch 1500 sebagai Pengikat dan Crospovidone sebagai Penghancur - Gunawan, Indra; Darsono, Farida Lanawati; Hermanu, Liliek S. (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2017)
Bastard cedar leaves (Guazuma ulmifolia L.) can lower cholesterol level on blood. Tannins and musilago are the components in bastar cedar leaves that play a role in lowering cholesterol. The purpose of this study was to determine the effect of starch 1500, crospovidone and its interaction on the physical quality of tablets. Tablets were made using wet granulation method. Optimization of tablet formulation consists of two factors. The first factor is the Starch 1500 which is used as a binder with the level (+1) that is 3% and the level (-1) that is 1.5%, and the second factor is the crospovidone used as disintegrant with the level (+1) that is 5% (-1) that is 2%. The response used is tablet hardness, fragility, and time of disintegration. The results of this study indicate that starch 1500 can increase the hardness, but can prolong the disintegration time of the tablet and can decrease the tablet fragility, while crospovidone can decrease the hardness, increase the fragility, and accelerated tablet disintegration time. The interaction of these two factors has a significant effect on tablet hardness, fragility and time of disintegration. The optimum formula was obtained with the combination of Starch 1500 2.22% and crospovidone 3.54% with estimated result of physical hardness test quality of 5.2Kgf; Fragility 0.643%; and disintegration time 11.54 minutes.